Eyeing for External Resources: Wants and Ways - Adhikary, Dileep K (NCWA Annual Journal, 2024)
External resources have shaped the making and breaking of the nations. In the past, the rulers dominated the source or provider of external resources while in the present days, the rulers (political leaders) are under the domination of resource providers (be it a government, agency or company). In the period following World War II, the United States rose to prominence politically and economically. The 21st century is seeing the rise of China. This study deals with the methods and practices relating to foreign aid and investments that have evolved and looks into their hold on Nepal. The study shows that the availability of external resources started with a goodwill approach. However, over time it has moved onto the sphere of influence of the resource providers while the governance failure has made the country more and more dependent on external resources failing to adopt safeguard measures.